Digital Divide and Learning Access for Papua Indigenous People: A Study at Secondary Schools in Sorong City - Zarni Adia Purna (ASHA Publishing, 2026)
This study investigates the digital divide and its consequences for learning access among Papua Indigenous People (Orang Asli Papua/OAP) students at secondary schools in Sorong City, West Papua Province, Indonesia. The digital divide refers to the gap between individuals who have effective access to digital technologies and those who do not, encompassing disparities in infrastructure, devices, skills, and meaningful use. Using a qualitative descriptive approach with in-depth interviews, observation, and documentation, this research examined the digital divide experience of OAP secondary school students, their teachers, and relevant education officials. Data were collected from 22 purposively selected informants across three state secondary schools with high OAP student enrollment in Sorong City. The findings reveal that OAP students face multidimensional digital exclusion: limited access to devices and internet connectivity at home, low digital literacy levels, a scarcity of culturally responsive digital learning content, and inadequate teacher capacity to facilitate technology-mediated learning. These barriers compound existing educational disadvantages and are widened during disruptions such as emergency remote learning. The study argues that the digital divide in OAP secondary education in Sorong City is not merely a technical or infrastructural problem but is deeply rooted in structural inequalities, historical marginalization, and cultural discontinuities between the state education system and OAP community life. Recommendations are offered for policy interventions to bridge the digital learning divide for OAP students through community-based digital access programs, culturally adapted digital content, and targeted teacher professional development.